Service Quality and User Satisfaction of Jaklingko Mikrotrans: Evidence From Jakarta’s Public Transport System - Fikri, Hafiz; Shalihati, Fithriyyah; Watazawwadu’ilmi, Sendy (Business Review and Case Studies, 2025)
Background: Traffic congestion in Jakarta disrupts mobility, productivity, and quality of life (QOL). As a solution, the Provincial Government of DKI Jakarta introduced the Mikrotrans service within the JakLingko program. However, despite the increasing number of users, complaints regarding punctuality, comfort, and driver behavior persisted. Purpose: This study evaluates user satisfaction with Mikrotrans’s services, identifies priority areas for service improvement, and proposes recommendations. Design/methodology/approach: A quantitative approach was applied using the SERVQUAL model to measure service quality gaps, Customer Satisfaction Index (CSI) to assess satisfaction, and Importance Performance Analysis (IPA) to prioritize improvements. Data were collected through structured surveys of Mikrotrans users. Findings/Result: The CSI score reached 79.83%, indicating a satisfied category, yet all attributes showed negative gaps. Importance-Performance Analysis (IPA) revealed four priority attributes falling into the Concentrate Here” quadrant: operational smoothness, driver competence, staff friendliness, and service accessibility, highlighting critical areas for immediate improvement. Conclusion: Although user satisfaction was achieved, systematic improvements are required. Recommendations include optimizing fleet management and arrival schedules, enhancing staff competence and ethics, upgrading and expanding bus stop facilities, standardizing service operations, and strengthening real-time scheduling and information systems. Originality/value (State of the art): This study integrates SERVQUAL, CSI, and IPA to provide a comprehensive framework for assessing user satisfaction with Jakarta’s Mikrotrans service, offering practical insights for PT JakLingko and policymakers to improve public transport in metropolitan contexts. Keywords: CSI, IPA, user satisfaction, Mikrotrans, SERVQUAL